Respon Industri Kecil Menengah (IKM) di Provinsi Jawa Timur Pada Kebijakan Sertifikasi Halal - Izzah Illiyyina; Arimurti Kriswibowo (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Policy implementation has changed along with policy-oriented learning with increasing knowledge of problem parameters and factors influencing policy changes. The government establishes a halal certification policy as a systematic step to provide halal safety guarantees for producers and consumers. The halal certification policy itself changed and reaped the pros and cons, especially on the obligation to have a halal certificate for business actors with halal raw materials. Small and medium scale industries actor’s are also directly affected by this policy. Therefore, this study aims to measure the response of small and medium industries in East Java Province. This study uses a descriptive quantitative method with a sample of 400 small and medium-sized industrial business actors in East Java Province. The results of the study indicate that the halal certification policy plays a significant role for small and medium industry business actors, but the majority of the 400 samples do not know that the halal certification policy has changed. This is a separate evaluation for the government to be more optimal in socializing policy changes because of these changes. It will mean a great deal to the communities concerned.